2021
DOI: 10.1371/journal.pone.0249874
|View full text |Cite
|
Sign up to set email alerts
|

Are underprivileged and less empowered women deprived of respectful maternity care: Inequities in childbirth experiences in public health facilities in Pakistan

Abstract: Background Attainment of healthcare in respectful and dignified manner is a fundamental right for every woman regardless of the individual status. However, social exclusion, poor psychosocial support, and demeaning care during childbirth at health facilities are common worldwide, particularly in low- and middle-income countries. We concurrently examined how women with varying socio-demographic characteristics are treated during childbirth, the effect of women’s empowerment on mistreatment, and health services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The discrepancy might be due to good commitment of health care professionals against physical abuse. This finding is similar with studies conducted in Pakistan and India on women's experiences of mistreatment during facility based childbirth (22,23) The odds of maternal disrespect and abuse among mothers who gave birth at night shifts were 2.2 times higher than those who delivered at day shifts [AOR=2.21; 95% CI:1.306, 3.772 ].This finding in line with study conducted in Kenya (17). In line with this, qualitative study conducted in Ethiopia revealed disrespectful and abusive care were more common during night shifts(4) .…”
Section: Discussionsupporting
confidence: 87%
“…The discrepancy might be due to good commitment of health care professionals against physical abuse. This finding is similar with studies conducted in Pakistan and India on women's experiences of mistreatment during facility based childbirth (22,23) The odds of maternal disrespect and abuse among mothers who gave birth at night shifts were 2.2 times higher than those who delivered at day shifts [AOR=2.21; 95% CI:1.306, 3.772 ].This finding in line with study conducted in Kenya (17). In line with this, qualitative study conducted in Ethiopia revealed disrespectful and abusive care were more common during night shifts(4) .…”
Section: Discussionsupporting
confidence: 87%
“…Women's level of education was significantly directly proportional to the level of observed RMC scores received in our study. Lack of education was also one of the primary determinants of mistreatment received by women during childbirth according to the WHO-supported study conducted across four countries [21] Higher levels of education and being gainfully employed would expectedly increase women's ability to demand their rights during childbirth and procure essential commodities for their birth [49]. In health facilities where essential birthing requirements are not freely provided to women, or where there are no financial protection schemes for women, non-procurement of these delivery materials has contributed to women's mistreatment during childbirth [30].…”
Section: Factors Associated With Observed Rmc Receivedmentioning
confidence: 99%
“…Mean score mistreatment was considered as key outcomes which is taken from a background study in similar setting that yielded a mean score of 25 (score range 0 to 40). A total of 308 postpartum women will be required to detect a statistical difference of 2.5-units decrease (or 10% reduction) in the mean score of mistreatment (from 25 [ 34 ] to 22.5) with standard deviation of 6 [ 34 ], 90% power, 5% level of significance, 2 design effect, and 10% lost-to-follow-up (LTFU) and/or non-response. We decided to proceed with a sample of 308 as it gives sufficient precision to perform range of additional analysis such as estimation of prevalence of different types of mistreatment and the effect of intervention on each of these types of mistreatment, while will not negatively affecting study timelines.…”
Section: Methodsmentioning
confidence: 99%